2019
DOI: 10.1177/0961203319881198
|View full text |Cite
|
Sign up to set email alerts
|

Complete heart block in lupus

Abstract: Conduction abnormalities are uncommon in adult patients with lupus. We present a young woman with recurrent syncope caused by third-degree atrio-ventricular block as the initial manifestation of lupus and review 31 additional cases of systemic lupus erythematosus patients that have been described previously with complete heart block. Heart blocks occurred almost exclusively in females. The median age was 37 years. In 24 cases heart blocks were diagnosed in patients with established lupus. In only five patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…We did not find any publications about conduction defects related to LS. In lupus erythematosus, conduction defects have been reported, but are uncommon ( 13 ). The aetiology is unclear, but the effects of autoantibodies reacting with the conduction system, myocardial disease, and adverse effects of antimalarials have all been suggested as a cause ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not find any publications about conduction defects related to LS. In lupus erythematosus, conduction defects have been reported, but are uncommon ( 13 ). The aetiology is unclear, but the effects of autoantibodies reacting with the conduction system, myocardial disease, and adverse effects of antimalarials have all been suggested as a cause ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…In lupus erythematosus, conduction defects have been reported, but are uncommon ( 13 ). The aetiology is unclear, but the effects of autoantibodies reacting with the conduction system, myocardial disease, and adverse effects of antimalarials have all been suggested as a cause ( 13 ). Autoantibodies might also be related to conduction defects in LS.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, we present a new and innovative use of the WiSE-CRT system in a patient with unfortunate complete heart block, likely a rare finding in systemic lupus erythematosus with positive anti-ribonucleoprotein antibodies. 5 The patient had multiple complex comorbidities, including end-stage renal disease necessitating hemodialysis. The patient had multiple transvenous ports over the years in the common iliac and subclavian veins bilaterally.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Natsheh et al researched case reports of CHB in lupus and found only four anti-Ro/SSA and two anti-La/SSB positive cases out of 32, therefore suggesting other possible pathophysiological mechanisms involved in SLE-induced conduction defects. Additionally, Natsheh et al discovered that 84% of CHB cases were anti-DNA positive and 100% were ANA positive [ 16 ]. Our patient’s anti-Ro/SSA and/or anti-La/SSB antibodies during the pregnancy period were also not elevated but both anti-DNA and ANA were positive.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient’s anti-Ro/SSA and/or anti-La/SSB antibodies during the pregnancy period were also not elevated but both anti-DNA and ANA were positive. Furthermore, a literature review of CHB cases with lupus erythematosus revealed that CHB almost exclusively involves women (30/32, 94%) and more importantly, the most common CHB manifestation in these women is syncope [ 16 ]. Since the probability of preexisting heart disease (such as ischemic heart disease, etc.)…”
Section: Discussionmentioning
confidence: 99%